Stromatolites from the Aptian Crato Formation, a hypersaline lake system in the Araripe Basin, northeastern Brazil - Warren, Lucas Verissimo [UNESP]; Varejao, Filipe Giovanini [UNESP]; Quaglio, Fernanda [UNESP]; Simões, Marcello Guimarães [UNESP]; Fuersich, Franz Theodor; Poire, Daniel Gustavo; Catto, Bruno; Assine, Mario Luis [UNESP] (Springer, 2017)
The origin of the Cretaceous laminites of the Crato Formation, Araripe Basin, northeastern Brazil, has been intensely debated since the beginning of the last century. The monotonous, up to 10-m-thick succession composed of very fine fossiliferous laminites in the middle of the unit lacked diagnostic features for assigning a chemically or biologically induced origin for this facies. The presence of a highly diverse and very well preserved alloch-thonous to parautochthonous fossil assemblage, associated with scattered halite pseudomorphs throughout the succession, led many authors to believe that these limestones were chemically deposited in a highly stressful, evaporitic shallow-water environment, such as a hypersaline lake close to marine environments. Recently, a micro-and ultrastructural analysis of the laminites yielded structures undoubtedly associated with a biological origin. Several examples of lithified in situ preserved coccoid and filamentous cells and extracellular polymeric substances suggest that the deposition of the laminated limestones was, at some levels, strongly influenced by microbial activity. Here, we record various examples of stromatolite microbialites (mounds, domes, and pseudo-columns) found at distinct stratigraphic levels in the middle part of the Crato Formation. Macro-, meso-, and microscopic features confirm the biologically induced mineralization and the existence of metabolic activity of microbes during the formation of the laminites. Biomat growth may also have played a major role in the excellent preservation of fossils in this famous Cretaceous Konservat-Lagerstatte from Brazil.
Keywords: Microbialites; Biologically induced carbonates; Santana Group; Lower Cretaceous; Aptian; Araripe Basin